Clinical Efficacy of Comprehensive Probiotic Therapy for Intestinal Dyspepsia Syndrome in Patients with Multiple Drug Resistant Tuberculosis with Co-morbid HIV Infection - A. A. Kholodov; E. O. Bryukhacheva; M. V. Primkulova; M. B. Lavryashina; T. V. Pyanzova (Туберкулез и болезни лёгких)
The objective: to evaluate main effects of complex probiotic therapy (CPT) in patients with multiple drug resistant tuberculosis and co-morbid HIV infection (MDR-TB/HIV) with intestinal dyspepsia syndrome (IDS) in the course of anti-tuberculosis treatment.Subjects and Methods. The study included 53 people with MDR-TB/HIV co-infection and clinically significant dyspeptic syndrome: 28 patients received a 30-day course of complex probiotic therapy and 25 patients received no such therapy. The effect of complex probiotic therapy on the course of dyspeptic and intoxication syndrome was assessed, and differences in hepatoprotective, hematopoietic, and immunogenic functions between the groups were studied. It was found out that patients receiving complex probiotic therapy had more effective relief of cytolysis, weakness and diarrhea, as well as a higher rate of weight gain, faster increase of hemoglobin concentration and CD4+ count. A clinical observation is presented that clearly demonstrates changes of these rates in a patient of TB hospital who received complex probiotic therapy.